Tissue and cellular distribution of gold nanoparticles varies based on aggregation/agglomeration status. (February 2012) - Keene, Athena M; Peters, David; Rouse, Rodney; Stewart, Sharron; Rosen, Elliot T; Tyner, Katherine M
Aim: The ability of nanoparticles to form larger superstructures of aggregates and agglomerates has been extensively noted in the literature. The in vivo biological impact of these structures, however, has not been assessed. This knowledge gap is especially critical in the safety assessment of nanoparticles to be used for therapeutic purposes.Method/results: Here we show that when administered intravenously into a mouse model, gold nanoparticle superstructures of reversible agglomerates and irreversible aggregates demonstrate significant differences in organ and cellular distribution compared with the primary particle building blocks. In addition, different structures produced different blood serum chemistry data.Conclusion: These findings raise the possibility for different mechanisms of toxicity between the structures. Such a possibility necessitates complete characterization and stability assessment of nanomaterials prior to their in vivo administration.